Bellas considerazions sobre ro prozeso de normatibizazión del aragonés - Quintana i Font, Artur (Caplletra. Revista Internacional de Filologia, 2002)
The author analyzes the role of Ribagorzan varieties on the creation of normative Aragonese. It can be observed that most of the traits of such varieties fail to appear in the accepted rules; this seems to stem not only from linguistic criteria, but rather from attitudes of méfiance catalane. Over the past years, a number of voices have called for greater attention to Ribagorzan varieties within normative Aragonese.